Handwriting Change in Breast Cancer Patients - Heba H Rohym; Ghada Mustafa Al-Galad; Noha Abdel Rahim Mohamad; Mohamed Ragab Teleb (Institute of Medico-legal Publications Pvt Ltd, 2021)
Background: Breast cancer is the most common cancer . In the course of cancer progression, there are specificneuromuscular disturbances that directly affect coordination. Handwriting is regarded as a vital constituentwhen it comes to the tracing of neuromuscular coordination. The Study aimed to study handwriting analysisin female cancer breast patients trying to find simple useful, non-invasive way help in early detection anddiagnosis and follow up of those patientsMethods: The study included 160 participants. The study participants were asked to write the same text (twoArabic sentences and her name in Arabic language) and draw lines in another paper, and then all handwritingsamples were scanned and examined.Results: Breast cancer patients age ranged from 30 – 76 years old with a mean ± SD of 50.3 ± 10.5.Patientsaccording to Educational level parameter were 5 groups; Illiteracy eradication program, primary ,middle,secondary, graduation and post gradates were 14 (8.75 %) , 10 (8.75 %) ,16(10 %),(80) 50 %,40 (25 %)respectively .By analysis of handwriting samples: Tremor, wide spaces between words, heavy writing pressure, slop orslant of writing upward slant or down slant and heaviness of Initial and terminal strokes were observed.After re-observation of pervious Handwriting changes and make a relation between these changes andcancer stages and lines of treatment which received, it was noticed that these changes were in samples ofpatient received multiple lines of treatment , in patients with metastasis or has another associated tumor asovarian, bladder cancers or lymphoma .Conclusion: There is no evidence of significant handwriting Changes in breast cancer samples unless patientreceived multiple lines of treatment , in patients with metastasis or has another associated tumor as ovarian,bladder cancers or lymphoma